Surgical trends, outcomes and disparities in minimal invasive surgery for patients with endometrial cancer in England: a retrospective cohort study. Issue 9 (16th September 2020) - Moss, Esther L.; Morgan, George; Martin, Antony P.; Sarhanis, Panos; Ind, Thomas
Abstract : Objective: To examine surgical outcomes and trends in the implementation of minimally invasive surgery (MIS) use for endometrial cancer (EC). Design: Retrospective cohort study. Setting: English National Health Service hospitals 2011–2017/2018. Population: 35 304 patients having a hysterectomy for EC identified from Hospital Episode Statistics. Methods: Univariate and multivariate analyses compared MIS to open hysterectomy (OH) by assessing the association between demographic, clinical and hospital characteristics by using logistic regression. A propensity score was created, to control for confounding factors including demographics, clinical and hospital characteristics, from a logistic regression which enabled the inverse probability weighting of treatment to be applied in order to compare outcomes of treatment. Main outcome measures: The association between route of surgery on perioperative morbidity and mortality. Results: The MIS rate rose from 40.3% in 2011 to 68.7% in 2017/2018, however, there was significant geographical variation (p<0.001). The overall 90-day mortality was significantly higher with OH versus MIS (OR 0.34, 95% CI 0.18 to 0.62, p=0.0002). MIS rates were significantly lower in patients from the lowest socioeconomic group (LSEG) compared with patients from the highest group (HSEG) (55.4% vs 59.9%, p<0.01), and in the black population as compared with white and Asian populations (40.4% vs 58.6% and 56.0%, p<0.0001). When patients from LSEG and black patients were treated in hospitals with high MIS rates, the MIS rate increased close to that of the HSEG and white patients (81.0% and 74.1% vs 83.2% and 82.6%). Conclusions: Further investigation is needed to understand the barriers to MIS and improve access so that as many patients as possible can benefit from the reduced morbidity/mortality associated with MIS.